Single-year change in views of democracy and society and support for political violence in the USA: findings from a 2023 nationally representative survey - Garen J. Wintemute; Sonia L. Robinson; Andrew Crawford; Elizabeth A. Tomsich; Paul M. Reeping; Aaron B. Shev; Bradley Velasquez; Daniel Tancredi (BMC, 2024)
Abstract Background A 2022 survey in the USA found concerningly high prevalences of support for and personal willingness to engage in political violence, of beliefs associated with such violence, and of belief that civil war was likely in the near future. It is important to determine the durability of those findings. Methods Wave 2 of a nationally representative cohort survey was conducted May 18-June 8, 2023; the sample comprised all respondents to 2022's Wave 1. Outcomes are expressed as weighted proportions; changes from 2022 to 2023 are for respondents who participated in both surveys, based on aggregated individual change scores. Results The completion rate was 84.2%; there were 9385 respondents. After weighting, 50.7% (95% confidence interval (CI) 49.4%, 52.1%) were female; weighted mean (SD) age was 48.5 (25.9) years. About 1 in 20 respondents (5.7%, 95% CI 5.1%, 6.4%) agreed strongly/very strongly that "in the next few years, there will be civil war in the United States," a 7.7% decrease. In 2023, fewer respondents considered violence to be usually/always justified to advance at least 1 of 17 specific political objectives [25.3% (95% CI 24.7%, 26.5%), a 6.8% decrease]. However, more respondents thought it very/extremely likely that within the next few years, in a situation where they consider political violence justified, "I will be armed with a gun" [9.0% (95% CI 8.3%, 9.8%), a 2.2% increase] and "I will shoot someone with a gun" [1.8% (95% CI 1.4%, 2.2%), a 0.6% increase]. Among respondents who considered violence usually/always justified to advance at least 1 political objective, about 1 in 20 also thought it very/extremely likely that they would threaten someone with a gun (5.4%, 95% CI 4.0%, 7.0%) or shoot someone (5.7%, 95% CI 4.3%, 7.1%) to advance such an objective. Conclusions In this cohort, support for political violence declined from 2022 to 2023, but predictions of firearm use in political violence increased. These findings can help guide prevention efforts, which are urgently needed.